Association between coronary spastic angina pectoris and obstructive sleep apnea - Tamura, Akira; Kawano, Yoshiyuki; Ando, Shinichi; Watanabe, Toru; Kadota, Junichi (Journal of cardiology, 2010)
Previous studies have shown a higher prevalence of obstructive sleep apnea (OSA) in patients with coronary artery disease than in control subjects. However, the association between coronary spastic angina pectoris (CSA) and OSA has not been investigated. Accordingly, we examined this association. We performed overnight polysomnography in 42 consecutive patients with CSA confirmed by an acetylcholine or ergonovine provocation test and in 20 age- and gender-matched control subjects. OSA was classified into the following three groups: mild OSA (5 ≤ apnea–hypopnea index [AHI] < 15); moderate OSA (15 ≤ AHI < 30); severe OSA (AHI ≥ 30). Patients with CSA had a greater AHI than control subjects (23.4 ± 16.3 vs. 10.1 ± 8.4, p = 0.001), and the prevalence of moderate-to-severe OSA was significantly higher in patients with CSA than in control subjects (66.7% vs. 20%, p = 0.001). A multivariate logistic regression analysis showed that moderate-to-severe OSA was independently associated with CSA (odds ratio 9.61, 95% confidence interval 2.11–43.78, p = 0.003). The prevalence of moderate-to-severe OSA was significantly higher in patients with CSA than in control subjects, and moderate-to-severe OSA was an independent factor associated with CSA, suggesting that OSA may be one predisposing factor for coronary spasm.